Louis Agassiz as a Teacher Illustrative Extracts on His Method of Instruction - Cooper, Lane (Cornell University Press, 2019)
By a succession of living pictures, as it were, this book shows the eminent naturalist in the very act of teaching. Sometimes he himself speaks, sometimes distinguished pupils of his reveal in their own words the process by which they were led to nature through direct and independent observation. The enthusiasm of their accounts is contagious. This collection of illustrative extracts on the ideals and practice of Louis Agassiz is probably unique in giving the actual methods of a great man of science in developing good students who could, in their turn, wisely instruct others. The book should be in the hands of all teachers, and of those who are preparing to teach. ; By a succession of living pictures, as it were, this book shows the eminent naturalist in the very act of teaching. Sometimes he himself speaks, sometimes distinguished pupils of his reveal in their own words the process by which they were led to nature through direct and independent observation. The enthusiasm of their accounts is contagious. This collection of illustrative extracts on the ideals and practice of Louis Agassiz is probably unique in giving the actual methods of a great man of science in developing good students who could, in their turn, wisely instruct others. The book should be in the hands of all teachers, and of those who are preparing to teach.